El destino de las remesas en el Ecuador: un análisis microeconómico sobre los factores que determinan su utilización en actividades de inversión - Viera Mendoza, Marlon Andrés (2009)
In the present work, the topic of remittances was analyzed from a microeconomic point of view. After the important role of the remittances in the national economy had already emphasized, we proceeded to investigate what are the main determinants that explain their investment degree at a national level; this mean, those factors that influence in the remittances recipient decision for consume or invest such income. The period of analysis cover the years 2007, 2008 and 2009. During the fieldwork, we found evidence that the majority of the remittances goes to current consume expenditures (75%) and only a 21% is destined to investment. Through an econometric model, it was possible to conclude that seven factors cause in a positive and direct form the investment percentage that a common remittances recipient can achieve in Ecuador. Taking in account the results of the model, the Ecuadorian representative recipient could invest until the 10% of the remittances received from rest of the world.